Long-Term Policy Options for the Palestinian Economy - World Bank (Washington, DC, 2013)
In light of deteriorating economic relations between Israel and the West Bank and Gaza, and suspended peace negotiations, it is timely at this juncture between the lapsed Interim Period and a final status agreement to examine past experience with a view to assessing the policy choices facing Palestinian policymakers in the future. The post-Oslo experience points to failed economic normalization and income convergence with Israel. Several reasons for these failures have been advanced, including poor implementation of the Paris Protocol, as well as fundamental flaws inherent to the protocol itself. The experience under the Paris Protocol illustrates the degree to which political and economic factors are intertwined; both types of factors need to be addressed in a comprehensive framework. The fact that political pressures from Israeli security concerns introduced severe economic hardship on the Palestinians and threatened newly-gained Palestinian autonomy contributed to the unraveling of the interim agreement. The economic environment of uncertainty, risk, costly transactions, and inadequate legal, regulatory and financial institutions hampered private sector development and especially Palestinian-Israeli partnerships and business networks at the firm level, effectively weakening an important tie that holds civil society together. These factors further undermined Palestinian economic growth, laying the foundation for political crisis and civil conflict. Given the problems associated with the existing policy framework, this analysis examines alternative policy options that will face Palestinian policymakers in the event of a peace agreement with Israel. These future policy choices relate to trade, labor mobility to Israel, and the business environment and associated public-private interactions. In a first stage, each policy area is analyzed separately, that is, in a partial equilibrium context independent of the others without accounting for broader intersectoral relationships. In a second stage, the analysis brings together these separate areas into an integrated framework. A range of assumptions vis-e-vis the nature of borders between West Bank and Gaza and Israel is delineated, tying together the trade, labor and private sector development considerations to measure their combined impact on growth prospects. The analysis develops scenarios to reflect different combinations of future policy options linked to the nature of borders with Israel. This simulation exercise illustrates the relative merits of each scenario, the associated trade-offs, and the prospects for economic growth in the event of a peace agreement and a completion of final status negotiations.